A new genus and species of the Mirine plant bug (Hemiptera: Miridae: Mirinae) from South Korea - Cho, Young Jae; Kwon, Yong Jung (Zootaxa, 2008)
This paper describes a unique new mirine plant bug collected in Jeollanamdo province and Gyeongsangbukdo province, South Korea. This mirid, which is represents a new genus of the tribe Mirini, exhibits external features such as an oval body, a vertex without transverse carina, an impunctate pronotum, and hemelytra that are shallowly punctate with blackish short pubescence. Although somewhat similar externally to certain species of the genus Lygocorides Yasunaga, the new mirid differs substantially with respect to the structure of the male genitalia; in particular, the vesica possesses a peculiar bundle of spinelike spicules and coiled-branched lobe-sclerites. Several external diagnostic characters also support the placement of this species into a new genus.